Biobotic motion and behavior analysis in response to directional neurostimulation - Dirafzoon, Alireza; Latif, Tahmid; Fengyuan Gong; Sichitiu, Mihail; Bozkurt, Alper; Lobaton, Edgar (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2017)
This paper presents preliminary results for motion behavior analysis of Madagascar hissing cockroach biobots subject to stochastic and periodic neurostimulation pulses corresponding to randomly applied right and left turn, and move forward commands. We present our experimental setup and propose an unguided search strategy based stimulation profile designed for exploration of unknown environments. We study a probabilistic motion model fitted to the trajectories of biobots, perturbed from their natural motion by the stimulation pulses. Furthermore, we provide a statistical assessment of the biobotic directional response to turn commands and its correlation with stimuli profile over time. This study paves the way towards reliable control for more realistic under-rubble search and rescue applications.